TUTURAN ALIH KODE DAN CAMPUR KODE DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VIII.6 DI SMP NEGERI 04 MAKASSAR: Code-Switching And Code-Mixing Utterances in Indonesian Language Learning Interaction Among Students of Class VIII.6 SMP Negeri 04 Makassar - Fitri Fahrezi, Muh; Hamsa, Akmal; Haliq, Abdul (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to describe the forms and functions of code-switching and code-mixing in Indonesian language learning interactions among eighth-grade students at SMP Negeri 04 Makassar. This study uses qualitative research with a descriptive research design. Data collection techniques include observation, recording, and listening and note-taking. The results showed that no data was found on code-switching, while code-mixing took the form of switching from the Makassar language to Indonesian and vice versa. Furthermore, no appropriate code-switching function was found in the data analysis method used, while the function of code-mixing in Indonesian language learning interactions among eighth-grade students at SMP Negeri 04 Makassar was to insert sentences and create familiarity. The sentence insertion function found in this study was the Makassar language affixes ji, mi, ki, and di as markers. The function of familiarisation in this study was that the speaker and interlocutor used more informal language to build a closer relationship.